Civic Entrepreneurship The Implementation of Civic Innovations in the Governance of the University of Zambia - Kanyamuna, Vincent (Advances in Social Sciences Research Journal, 2020)
The article titled "Civic Entrepreneurship: The Implementation of Civic Innovations in the Governance of the University of Zambia" is submitted for your publication. Waiting to hear from you.